SARS-CoV-2 vaccine excipients polyethylene glycol and trometamol do not induce mast cell degranulation, in an in vitro model for non-IgE-mediated hypersensitivity - Quan, Paola Leonor; Ollé, Laia; Sabaté-Brescó, Marina; Guo, Yanru; Muñoz-Cano, Rosa; Wagner, Annette; Gastaminza, Gabriel; Martín, Margarita (Frontiers in Allergy, 2022)
The development of vaccines against SARS-CoV2 brought about several challenges, including the management of hypersensitivity reactions to these formulations. The search for underlying mechanisms involved in these adverse events initially focused on excipients which may trigger mast cell activation responses via non-IgE pathways: polyethylene glycol and trometamol. We sought to determine whether these components, in their pure form, were capable of stimulating mast cells directly. To test this hypothesis, we used an in vitro model for non-IgE-mediated activation that has previously shown degranulation responses induced via MRGPRX2 with known drug agonists of the receptor. Human LAD2 mast cells were incubated with different concentrations (1, 10, 50 mg/ml) of trometamol and of purified polyethylene glycol/Macrogol (molecular weights: 2,000, 3,350, 4,000, and 6,000). Mast cell degranulation was assessed using a beta-hexosaminidase read-out. Interestingly, degranulation responses for all reagents tested showed no significant differences from those obtained from the negative control (basal degranulation). Receptor-silencing assays were therefore not conducted. In summary, purified PEG and trometamol did not induce mast cell degranulation in this in vitro model for the study of non-IgE mechanisms of drug hypersensitivity, previously shown to be useful in the investigation of MRGPRX2 ligands. Studies using complete vaccine formulations, lipid conjugates, and receptor gene variants are needed to further clarify mechanisms of vaccine hypersensitivity.